Electrospray Ionization Mass Spectrometry Characterization of Musts and Alembic Brazilian Cachaças Using Selected Yeast Strains. Issue 4 (April 2014) - Badotti, Fernanda; Gomes, Fátima C.O.; Teodoro, Mariana M.G.; Silva, Alisson Luiz Diniz; Rosa, Carlos Augusto; Machado, Ana Maria de R.
Abstract The choice of fermentation system during cachaça production can greatly influence the chemical composition of the beverage. In this work, Saccharomyces cerevisiae strains were selected based on fermentative properties and used as starters to produce alembic cachaça. In distillery scale production, the selected yeast strains exhibited greater adaptiblity to the fermentation environment and hence remained predominant throughout the process. Electrospray ionization mass spectrometry in the negative ion mode revealed that most of the compounds present in the must are different from those formed in the distillate for both cachaças obtained from spontaneous and selected strains. However, beverages produced using selected strains showed greater similarity in chemical profiles than those produced from spontaneous strain fermentation. Moreover, a smaller number of ions were detected in beverages produced by selected strain than from spontaneous strain fermentation. Our results indicate that the selected S. cerevisiae strains evaluated are able to produce cachaças less subject to variation in chemical composition. This could potentially improve brand consistency and thus commercial viability, particularly in the international market.